Dewey's theory and its contributions for Science Teaching (Research, Society and Development, 2022)
Through this work, we sought to present aspects related to John Dewey's life and theory, highlighting elements referring to scientific problems arising from common sense; the individual's experience and contributions to cognitive development; the importance of the development of democracy in the school context and the teaching by investigation defended by the school conceived by Dewey. Through this study, the importance that relationships and experiences in a cultural environment acquire for the improvement of an individual's knowledge is identified. Accordingly, teaching for Dewey suggests being mediated through problem solving, involving situations that are part of the students' reality, bringing school concepts closer to their daily lives and helping them to create the habit of seeking solutions to the issues that worry them. in and out of school.